PERFORMANCE EVALUATION OF OLSR IN WIRELESS MESH NETWORK - YEVERSON DOO (NIM 23204075); Pembimbing: Dr. Ir. Hendrawan dan Ir. Nana Rahmana, M.Eng., SAMY
Wireless Mesh Network (WMN) consists of two types of nodes: mesh routers and mesh clients. Mesh routers have minimal mobility and form the backbone of WMNs whereas mesh clients can be either stationary or mobile and form a client mesh network among themselves and with mesh routers. The integration of WMN with other networks such as the internet, cellular, IEEE 802.11, IEEE 802.15, IEEE 802.16, sensor networks, etc., can be accomplished easily through the gateway and bridging function in the mesh router. Deploying a WMN is not too difficult, because all the required components are already available in the form of ad hoc network routing protocol, IEEE 802.11 MAC protocol, wired equivalent privacy (WEP) security, etc. Several kinds of ad hoc routing protocols have been considered to be used in WMN. Optimized Link State Routing (OLSR) protocol is one of them. OLSR is a proactive link state routing protocol that always updates networks changes through broadcasting control packet periodically. The aim of this research is to tune the time interval of OLSR control packet; which are Hello packet and Topology Control (TC) packet so that the compatible time interval standard can be achieved in client mesh network. There are two scenarios used: 25 nodes for small networks and 50 nodes for the large ones. The amount of connection is 10 and 20 for the first scenario, 20 and 40 for the second scenario. The types of traffic used are CBR, TCP or both. The result shows that for CBR traffic, 1 second Hello interval is the best result. When TCP traffic is used, the best Hello interval is 3 seconds. Considering the result of throughput, packet drop and packet control, Hello interval of 2 seconds and TC interval of 7 seconds give better result than standard interval OLSR.